Model informed dose regimen optimizing in development of leritrelvir for the treatment of mild or moderate COVID-19 - Wang, Kun; Li, Haijun; Li, Youyun; Xu, Fengyan; Sun, Zhongyi; Yang, Yuting; Huang, Jufang; Chen, Xiaoxin (Frontiers in Pharmacology, 2024)
Leritrelvir (RAY1216) acts as a main protease inhibitor that hinders the cleavage of viral precursor proteins, thereby inhibiting virus replication of SARS-CoV-2) . This antiviral mechanism has shown significant efficacy against the novel coronavirus.Preclinical studies have demonstrated the potent antiviral activity and favorable safety profile of this compound.This study presents a pharmacokinetic model for leritrelvir, with and without ritonavir as a pharmacokinetic enhancer, based on plasma concentration data from a phase I trial involving 72 subjects in single-ascending dose (SAD), multiple-ascending dose (MAD), and a food effect cohort. Analysis was conducted using a nonlinear mixedeffects model, and clinical trial simulations were carried out to evaluate the necessity of co-administration with ritonavir and to investigate different dosage regimens.The findings of this study demonstrate a favorable safety profile for leritrelvir. With simulation suggests that a 400 mg thrice daily (TID) regimen may be optimal to maintain the trough concentrations (Ctrough) above levels required for inhibiiting viral replication. While ritonavir was found to enhance exposure, it was deemed unnecessary. Gender and food consumption were identified as significant covariates affecting pharmacokinetic parameters, however, no dose adjustments were deemed necessary. Subsequent phase II and phase III trials validated the appropriateness of a 400 mg TID regimen for the administration of leritrelvir.